Impaired graft survival in kidney transplants from expanded criteria donors with HLA-DR mismatch - Scheuermann, Uwe; Rhode, Philipp; Lehmann, Claudia; Kowald, Jan; Seiffer, Sophie; Haak, Fabian; Seehofer, Daniel; Rabe, Sebastian Murad; Tautenhahn, Hans-Michael (Frontiers in Transplantation, 2026)
Human leukocyte antigen (HLA)-DR mismatches are known to increase the risk of graft rejection following kidney transplantation (KT). Especially in KT using grafts of lower quality from expanded criteria donors (ECD), the immune response plays a critical role. Therefore, the aim of this study was to investigate the impact of HLA-DR mismatches on both short- and long-term outcomes in primary ECD KT. 537 KT recipients were stratified into four groups based on their HLA-DR mismatch status [absent (−) or present (+)] and donor type [standard criteria donor (SCD) or ECD]: (1) SCD-DR-(N = 126), (2) SCD-DR+ (N = 167), (3) ECD-DR- (N = 60) and (4) ECD-DR+ (N = 184). Clinicopathological characteristics, transplant outcomes and survival were evaluated across the groups. Rejection-free graft survival was significantly decreased in recipients of ECD-DR + KT (P = 0.005). In comparison with ECD-DR- KTs, ECD-DR + KTs were associated with a significantly reduced graft survival (15.1 vs. 10.7 years; P = 0.034). After adjusting for relevant cofactors using multivariate Cox regression analysis, HLA-DR mismatch remained an independent predictor of graft rejection and graft survival in ECD kidney grafts. These results suggest that HLA-DR compatibility should be considered in allocation protocols for this donor category to improve long-term outcomes.